Linguistic Stereotyping in Older Adults' Perceptions of Health Care Aides. Issue 7 (2nd July 2016) - Rubin, Donald; Coles, Valerie Berenice; Barnett, Joshua Trey
ABSTRACT: The cultural and linguistic diversity of the U.S. health care provider workforce is expanding. Diversity among health care personnel such as paraprofessional health care assistants (HCAs)—many of whom are immigrants–means that intimate, high-stakes cross-cultural and cross-linguistic contact characterizes many health interactions. In particular, nonmainstream HCAs may face negative patient expectations because of patients' language stereotypes. In other contexts, reverse linguistic stereotyping has been shown to result in negative speaker evaluations and even reduced listening comprehension quite independently of the actual language performance of the speaker. The present study extends the language and attitude paradigm to older adults' perceptions of HCAs. Listeners heard the identical speaker of Standard American English as they watched interactions between an HCA and an older patient. Ethnolinguistic identities—either an Anglo native speaker of English or a Mexican nonnative speaker–were ascribed to HCAs by means of fabricated personnel files. Dependent variables included measures of perceived HCA language proficiency, personal characteristics, and professional competence, as well as listeners' comprehension of a health message delivered by the putative HCA. For most of these outcomes, moderate effect sizes were found such that the HCA with an ascribed Anglo identity—relative to the Mexican guise—was judged more proficient in English, socially superior, interpersonally more attractive, more dynamic, and a more satisfactory home health aide. No difference in listening comprehension emerged, but the Anglo guise tended to engender a more compliant listening mind set. Results of this study can inform both provider-directed and patient-directed efforts to improve health care services for members of all linguistic and cultural groups.